In vitro evaluation of the influence of titanium nitride coating on the retention force between components of two-part abutments - Nadine Freifrau von Maltzahn; Jan Holstermann; Meike Stiesch; Philipp Kohorst (BMC, 2021)
Abstract Background Two-part abutments are typically made up of a base composed of titanium and a ceramic build-up. The long-term outcomes are affected by the mechanical durability. The purpose of the present investigation was to evaluate and compare the retention force of two-part abutment systems with titanium or titanium nitride bases-as fixed with zirconia components and with various surface treatments. Methods A total of 60 two-part abutments were investigated-with a titanium base (n = 30) or titanium nitride coated bases (n = 30) and bonded with zirconia ceramic build-ups. The bonding surfaces were treated with aluminium oxide blasting, with an average particle size of 110 µm. The titanium bases were then pretreated with Alloy Primer or Clearfil Ceramic Primer. The ceramic build-ups were only treated with Clearfil Ceramic Primer. For twenty test specimens, no chemical pretreatment was performed. Test specimens were classified into six groups in accordance with the pretreatment (A-F; n = 10). A resin-based luting agent was employed to attach the two parts. Specimens were then subjected to artificial thermal aging (104 cycles with 5 °C/55 °C). The retention force between the two parts was then investigated with a pull-off test. The findings were analyzed by ANOVA statistics. Fracture patterns were examined by electron microscopy. Results In the absence of primer, titanium nitride coated bases gave significantly greater retention forces than other samples (p < 0.05). Chemical preconditioning with silane coupling agents did not effect on the retention force of coated bases. Conclusions The results of the current study suggested that modifying metal surfaces by coating the base with titanium nitride not only has esthetic and biological advantages, but also enhances the mechanical properties of the adhesive bond of two-part abutments.